A revista que pode deixar em sua casa porque não há perigo de perversão : a representação da mulher nas colunas da revista Jornal das Moças (1930-1945) - Albuquerque, Dálete Cristiane Silva Heitor de (2016)
At the beginning of the Vargas Era, the political scenario was the conquest by female's vote. The government would create an electoral code, in which women with certain profiles would have the legal right to vote. However, from the Code of 1932, the female right to vote was extended to all women and also, from the pressures made by feminists both men’s vote and women’s vote became equal. Despite this struggle scenario, there was an established female model, maintained and disseminated. And, the press, especially women's press, played an important role to maintain this model of woman, being this woman if not the principal, is one of the main contributors of Vargas government and the State. And it was necessary a special treatment to the formation and education of this woman. It would be necessary to establish a difference between men and women education project, since referring to men, it was essential to prepare them to a moral, political and economic life of nation, and for women the "fate that Providence has given them." So, man had an education aimed to militancy, to public life, to business. For woman, the education was aimed to play a role at home, mother that would educate children in the same purposes in which she was formed. This research aimed to identify the representations of women existing in a female textual support, whose main objective was to bring to carioca families a moral content by letters, columns, poems, recipes, illustrations and other genres that would help in a possible hidden project of women-formation. The textual support chosen is the weekly magazine Jornal das Moças, published between 1914-1965. The corpus consists of the publications from 1932 to 1945, in the Vargas Era, assuming that the magazine Jornal das Moças would have been one of the means in which this dictatorial government could establish its ideological discourse. It is important to understand that speeches made in the context experienced by the subjects or magazine consumer groups are not neutral. They are indeed producers of imposed practices to each other, in struggles, struggles of representations in order to legitimize their choices. The theoretical and methodological framework used was based in the concept of Representations, Reading Protocols of Roger Chartier, situating the study within the Cultural History and the History of Reading. It was also used the concept of Model-Reader of Umberto Eco, because it is underatood that this concept helped the investigation, as support to the concepts of reading protocols, as understanding of the construction of a textual strategy of the model-reader in the magazine analyzed, and consequently, in representations of woman towards consumption and also representations of desired woman. All of this, in order to lead to a construction of housewife profile and such discourse would set as an instrument of speech of mechanisms for establishing dominant ideologies of a given period by a mythologizing game during the Vargas dictatorship. It was observed that the magazine evoked an identity match between the reader woman, the author and his/her established speech. The authors and publishers, and all professionals involved in the production process of the magazine, in turn, built a facet or facets, from a representation of reality or the setting of a reality desired to the reader. In this play, it would be cheating, omission, value judgements by the speech established to offer to readers, and mainly women readers, the representations that would form the alleged strong state of Vargas nation. In a superficial analysis of some last numbers of the magazine, that are beyond of 1932-1945 period, it was evident that the magazine continued with a closed-formation project for woman, her modesty, and also show a woman faced to the care of family and home. And, in middle 60s it would be difficult to survive in the labor market, considering that a new feminist movement was happening. And that movement would set shortly. And the reflections of this this movement should already be felt. They were fighting not just for female education, but also for the expansion of labor rights, sexuality, the relationship with the body, the divorce, in addition to the struggle for the total absence of gender-defined hierarchy.